Challenges Associated with Semen Quality While Collecting Beef Bulls for Semen Freezing - A. R. Hartman; N. M. Goodenow; S. K. Tucker; K. E. Fike; D. M. Grieger (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to evaluate the frequency of failure to freeze semen due to semen quality. Study Description:Semen collection data from 2008 to 2018 were obtained from the Kansas Artificial Breeding Services Unit and consisted of 14,750 ejaculates from bulls. Bulls were collected twice weekly on Mondays and Thursdays with an artificial vagina. Bulls not receptive to the artificial vagina were subject to electro-ejaculation. A single technician was responsible for all pre-freeze and post-thaw semen analysis. Ejaculates were required to meet quality standards for both progressive motility and morphology. Results:Over the ten years, 21% of ejaculates met all freezing quality standards, 11% of all ejaculates collected did not have a high enough motility to be considered satisfactory for a breeding soundness exam (BSE), and 63% of all ejaculates did not reach the motility quality threshold for freezing. Ejaculates from bulls ≤ 12 months of age produced ejaculates that would not meet satisfactory levels of a BSE 15% of the time. Ejaculates from bulls 13–18 months of age produced unsatisfactory ejaculates for motility for a BSE 6% of the time. When evaluating primary sperm abnormalities, 87% of ejaculates had less than 20% primary sperm abnormalities. Ejaculates from bulls ≤ 12 months of age produced the highest amount of ejaculates failing due to primary abnormalities with 24%, while bulls ≥ 31 months of age produced the least amount of ejaculates failing due to primary abnormalities at 10% of ejaculates. When evaluating total sperm abnormalities per ejaculate, 77% of ejaculates met the threshold of less than 30% total abnormalities. Ejaculates from bulls ≤ 12 months of age failed to meet the total sperm abnormality threshold 28% of the time. These results highlight one of the main difficulties of collecting freezing quality semen, in which semen meets the standards of normal spermatozoa but where most samples do not meet needs for progressive motility. The Bottom Line:Of over 14,000 collections, only 21% met all requirements for freezing semen, approximately 63% did not meet progressive motility freezing standards, and 11% did not meet the satisfactory level of a BSE.
Keywords: breeding; soundness exam; motility; sperm abnormalities